Manufacturing Nanostructured and Microstructured Chitosan Prepared By Milling Shrimp Shell (European Journal of Engineering Science and Technology, 2019)
Nano-products are of great interest in the field of pharmaceutical, corrosion, medicine, and engineering. This research aimed to produce nano-chitosan. Nanocrystallite. Shrimp shells have been prepared by using a high-energy planetary ball with optimal rotational speed. The raw material was subjected to standard chemical processing for chitin extraction, followed by deacetylation to obtain nanocrystallite chitosan, which is characterized by Scanning Electron Microscope SEM Fourier, Transform Infrared Spectrometry FT-IR and X-ray diffraction (XRD).